2014
DOI: 10.1039/c4cp00236a
|View full text |Cite
|
Sign up to set email alerts
|

Non-symmetric 9,10-diphenylanthracene-based deep-blue emitters with enhanced charge transport properties

Abstract: Realization of efficient deep-blue anthracene-based emitters with superior film-forming and charge transport properties is challenging. A series of non-symmetric 9,10-diphenylanthracenes (DPA) with phenyl and pentyl moieties at the 2nd position and alkyl groups at para positions of the 9,10-phenyls were synthesized and investigated. The non-symmetric substitution at the 2nd position enabled to improve film forming properties as compared to those of the unsubstituted DPA and resulted in glass transition tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 47 publications
7
49
0
Order By: Relevance
“…Absorption spectra of all 2,9,10-arylanthracene derivatives resembles those of unsubstituted anthracene [47] as well as its derivatives like 2-phenylanthracene [49] and other similar anthracene derivatives [26]. The absorption spectra of 2,9,10-arylanthracene compounds in solid state are redshifted for about 120-130 meV and slightly broadened in respect to those of in dilute solutions.…”
Section: Optical Propertiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Absorption spectra of all 2,9,10-arylanthracene derivatives resembles those of unsubstituted anthracene [47] as well as its derivatives like 2-phenylanthracene [49] and other similar anthracene derivatives [26]. The absorption spectra of 2,9,10-arylanthracene compounds in solid state are redshifted for about 120-130 meV and slightly broadened in respect to those of in dilute solutions.…”
Section: Optical Propertiesmentioning
confidence: 98%
“…The additional substitution at the 2 nd position also helps to ensure amorphous state and improves charge transport properties of the films [10,30]. However the additional π-conjugation extension towards the long axis of the molecule results in the reorganization of singlet and triplet energy levels when the T n level emerges below S 1 leading to the efficient ISC recombination and low Φ F [26]. Despite the importance of the intersystem crossing, recent studies have suggested that the vibrational relaxation may also be the important pathway for the non-radiative decay in anthracene derivatives [31,32].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is worth noting that increasing compound concentration up to 10 wt % (for benzofluorenes) or 20 wt % (for fluorenes) had negligible influence on the U F and s, whereas further increase of the concentration up to 100 wt % resulted in roughly 2-fold drop of these values. Only 2-fold reduction of U F and s in the neat films is caused by enhanced nonradiative relaxation induced by exciton migration and infers rather weak emission quenching 7,16,17 and thereby weak intermolecular coupling. This was also confirmed by the small red shift of emission spectra as well as single exponential decay of the transients preserved up to the highest oligomer concentrations in PS.…”
mentioning
confidence: 99%